ACCOUNTING PRACTICES AS A STRATEGIC TOOL FOR THE SUSTAINABILITY OF MICROENTERPRISES: A STUDY IN HUMAITÁ/AM - Góes, Ronald Prestes; Moçambite, Viviane da S. Costa Novo; Fonseca, Marcello Pires; da Cunha, Edileuza Lobato; Moreira, Giovanna Costa Novo; da Silva, Aldenor Moçambite; da Silva Filho, Giovani Caldas (Seven Editora, 2025)
This study analyzes the importance of accounting practices as a strategic tool for the sustainability of microenterprises in Humaitá, Amazonas. The research seeks to highlight the correlation between the effective implementation of accounting practices and the financial performance of these companies, considering the challenges faced by them, such as lack of financial planning and inadequate management. Through a descriptive and qualitative methodology, with literature review and application of questionnaires to microentrepreneurs in the region, the study aims to identify effective accounting practices, challenges faced and propose solutions to improve accounting management. The results are expected to contribute to local economic development, offering valuable insights for entrepreneurs and public policy makers, in addition to fostering the sustainability of microenterprises in Humaitá. DOI: https://doi.org/10.56238/sevened2024.037-202